2010
DOI: 10.1139/b09-109
|View full text |Cite
|
Sign up to set email alerts
|

Floral nectary structure, nectar production, and carbohydrate composition in theLiliumAsiatic hybrid ‘Trésor’

Abstract: Floral nectary structure, nectar production, and carbohydrate composition were compared from petals (''inner tepals'') and sepals (''outer tepals'') of Lilium Asiatic hybrid 'Trésor' (Liliaceae). The six nectaries each occupied a narrow furrow bordered by two convergent ridges extending adaxially from the petal and sepal base. Each sepal nectary furrow was shorter and more concealed. In both nectary types, many vascular bundles comprising xylem and phloem supplied 5.5-8 layers of nectariferous parenchyma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…showed that fructose was distinctly dominant to glucose. Conversely, in Lilium, sucrose was the most abundant nectar sugar (Stolar and Davis 2010). These results can probably be attributed to differences in pollinating agents, but field data for many Fritillaria and Lilium species are unfortunately scarce.…”
Section: Nectar Secretion and Resorptionmentioning
confidence: 94%
See 4 more Smart Citations
“…showed that fructose was distinctly dominant to glucose. Conversely, in Lilium, sucrose was the most abundant nectar sugar (Stolar and Davis 2010). These results can probably be attributed to differences in pollinating agents, but field data for many Fritillaria and Lilium species are unfortunately scarce.…”
Section: Nectar Secretion and Resorptionmentioning
confidence: 94%
“…However, nectary morphology are similar, irrespective of their position, and any variation in secretory activity might result from the somewhat larger tepals of the inner whorl. On the other hand, the Lilium hybrid Trésor displays a clear distinction between the perianth segments, but each petal and sepal produces a comparable amount of nectar sugars (Stolar and Davis 2010).…”
Section: Nectar Secretion and Resorptionmentioning
confidence: 99%
See 3 more Smart Citations